1976
DOI: 10.1083/jcb.71.2.472
|View full text |Cite
|
Sign up to set email alerts
|

Association of a protease (plasminogen activator) with a specific membrane fraction isolated from transformed cells.

Abstract: The intracellular distribution of a specific protease, plasminogen activator (P,~/), has been examined in Rous sarcoma virus-transformed chick embryo fibroblasts (RSV-CEF). Cellular homogenates were fractionated by differential centrifugation followed by sucrose gradient centrifugation. The activities and the percent distribution of a series of marker enzymes, specific for different subcellular organelles, were compared to those of PA. Normal CEF have been similarly fractionated and the relatively low amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
0

Year Published

1977
1977
1996
1996

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(73 citation statements)
references
References 55 publications
4
69
0
Order By: Relevance
“…The pattern of cellular distribution also differs, with granular/punctuate positivity in endothelium and uniform surface reactivity in the few parenchymal cells that reacted. These observations are consistent with some of the activity being lysosomal in endothelial cells as has been found in other species and tissues (Ali & Lack, 1965), and the finding that in vitro tumour cell PA is membrane associated (Quigley et al, 1976).…”
Section: Discussionsupporting
confidence: 79%
“…The pattern of cellular distribution also differs, with granular/punctuate positivity in endothelium and uniform surface reactivity in the few parenchymal cells that reacted. These observations are consistent with some of the activity being lysosomal in endothelial cells as has been found in other species and tissues (Ali & Lack, 1965), and the finding that in vitro tumour cell PA is membrane associated (Quigley et al, 1976).…”
Section: Discussionsupporting
confidence: 79%
“…In a number of published studies of cells other than neutrophils, PA was found in the plasma membrane or plasma membrane-like structures (8,11,12), but in view of our findings, which clearly show that other cell proteases may have a crucial effect on the quantity and the distribution of PA, these results should be reexamined .…”
mentioning
confidence: 78%
“…In spite of these observations, it has been difficult to demonstrate that Pmg As are actually synthesized in this tissue (9). The (27,28), possibly with the plasma membrane (11). Intracellular Ping A was found to exist in a latent form that could be revealed by brief, controlled acidification.…”
mentioning
confidence: 95%